The frequency of antlerless female caribou and reindeer in Alaska - Cronin, Matthew A.; Haskell, Shawn P.; Ballard, Warren B. (Rangifer, 2003)
The presence or absence of antlers in female caribou and reindeer may reflect genetic or nutritional effects. We classified antler status of female caribou of the Alaska Central Arctic Herd in 1994, 1995, and 2002, and female reindeer in two captive Alaskan herds in 1994. Of 3091 female caribou classified during three years, 152 (4.9%) were antlerless. Frequency of antlerless females in the Central Arctic Herd was similar to that of other Alaskan caribou herds. There were no antlerless females among 231 classified captive reindeer. We compared the frequency of antlerless females in the Alaskan herds with other herds, and possible nutritional and genetic influences on female antler status are discussed.